2014
DOI: 10.1007/s00134-014-3276-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of insufficient amikacin peak concentration in critically ill patients receiving a 25 mg/kg total body weight regimen

Abstract: Despite an amikacin dose of 25 mg/kg of total body weight, 33% of patients still had an amikacin Cmax < 60 mg/L. Positive 24-h fluid balance was identified as a predictive factor of Cmax < 60 mg/L. When total body weight is used, low BMI tended to be associated with amikacin underdosing. These results suggest the need for higher doses in patients with a positive 24-h fluid balance in order to reach adequate therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
68
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 27 publications
11
68
1
1
Order By: Relevance
“…Several studies have reported that the pharmacokinetics of aminoglycosides are altered in critically ill patients, leading to a C max lower than the targeted C max in 30 to 40% of critically ill patients using standard dosing regimens (24)(25)(26)(27). The increased volume of distribution observed in critically ill patients and the concentration-dependent killing activity of aminoglycosides support the use of regimens with higher doses of amikacin to achieve adequate C max s. The use of dosing regimens of Ն25 mg/kg in critically ill patients has been suggested by several authors and recommended by some national guidelines (13,24,27,28). However, some concerns remain about aminoglycoside-related nephrotoxicity using high aminoglycoside dosing regimens, especially in patients with AKI requiring RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the pharmacokinetics of aminoglycosides are altered in critically ill patients, leading to a C max lower than the targeted C max in 30 to 40% of critically ill patients using standard dosing regimens (24)(25)(26)(27). The increased volume of distribution observed in critically ill patients and the concentration-dependent killing activity of aminoglycosides support the use of regimens with higher doses of amikacin to achieve adequate C max s. The use of dosing regimens of Ն25 mg/kg in critically ill patients has been suggested by several authors and recommended by some national guidelines (13,24,27,28). However, some concerns remain about aminoglycoside-related nephrotoxicity using high aminoglycoside dosing regimens, especially in patients with AKI requiring RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Two amikacin concentrations are measured, at 1 to 2 h and at 8 to 10 h after the end of infusion of this first dose, to permit dose individualization (6). Recent clinical studies corroborate this approach by suggesting that an initial amikacin dose Ն25 mg/kg is likely needed as empirical therapy of certain Gramnegative infections (7)(8)(9)(10). Herein, we report on the amikacin exposure profile observed in our patients with this higher-thanregulatory-approved amikacin treatment strategy (1).…”
mentioning
confidence: 99%
“…Nevertheless, achieving the corresponding serum concentrations of AMK in patients is unlikely with conventional dosing of 15 mg/kg body weight/day. AMK doses exceeding 25 mg/kg/day may achieve serum drug levels of Ն60 g/ml, which approaches concentrations of 4ϫ the MIC for strains with MICs of 16 but not 32 g/ml (12)(13)(14).…”
mentioning
confidence: 99%